Peran Media Sosial Instagram Dinas Pariwisata Kota Samarinda Sebagai Media Promosi Pariwisata Selama Pandemi Covid-19 - Mohammad Tahta Aji Surya Nusantara (Jurnal Administrasi Bisnis Fisipol Unmul, 2022)
The tourism office of the City of Samarinda is an element of local government staff led by the head of the service who is under the Mayor and is responsible to the Mayor of Samarinda. This study aims to determine the role of social media Instagram of the tourism office of Samarinda City as a medium for tourism promotion during the Covid 19 Pandemic, supporting factors, and inhibiting factors of social media Insagram of the Samarinda City tourism office during the Covid 19 Pandemic. This type of research is descriptive qualitative. Sources of research data are key informants, and related informants in this study. The data collection techniques in this study were methods, interviews, documentation, and literature studies. The data analysis technique used is data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Samarinda City tourism office Instagram carries out tourism promotion using social media such as: Instagram, Facebook, Twitter, and Youtube. In addition, in the midst of the Covid-19 pandemic, tourism activities are also carried out, especially in the city of Samarinda. Supporting factors for the wider community, especially followers of @dispar.samarinda can see the activities held by @dispar.samarinda through available social media. And the inhibiting factor is the lack of a collection of photos and videos during the Covid-19 Pandemic which affects the performance of @dispar.samarinda in carrying out tourism promotion activities.